Promoting Economic Growth and Environmental Sustainability through Energy Efficiency: Evidence from Indonesia - Tenrini, Rita Helbra; Damayanty, Sofia Arie; Setyawan, Dhani; Setiawan, Hadi; Rakhmindyarto, Rakhmindyarto (International Journal of Energy Economics and Policy, 2021)
Indonesia has set a unilateral greenhouse gas emissions (GHG) reduction target by 29% and conditional targets with international support of up to 41%, compared to the business as usual by 2030. This paper aims to formulate energy conservation policies to increase productivity and promote economic growth in Indonesia. Indonesia’s energy conservation policy has multiple aspects: supporting energy security, commitment to GHG emission reduction, state budget efficiency, and improving productivity and competitiveness. Using Social Accounting Matrix (SAM), this study found evidence that energy efficiency saving will positively affect ecological sustainability and economic agents in the five targeted sectors: energy, waste, industrial processes, and production use, agriculture, and forestry. Furthermore, the Corporate Social Responsibility (CSR) policy provides positive effects in increasing economic growth and reducing income disparities. Keywords: Energy Conservation, Energy Efficiency, Economic Growth, Environmental Sustainability. JEL Classifications: Q40, O40, Q56 DOI: https://doi.org/10.32479/ijeep.11463